Wuthuga (dugong) population status in Gathaagudu (Shark Bay) sea country - Holly Raudino; Amanda Hodgson; Chris Cleguer; Kym Reeve; Molly Moustaka; Osmar Luiz; Simone Strydom; Kathy Murray; Neilisha Oakley; Tariq McDonald; Abby Leyendekkers; Jay Hayes; et al. (Frontiers in Marine Science, 2026)
Introduction Monitoring trends in wildlife populations and their response to pressures is integral but challenging for conservation managers. Wuthuga (dugongs (Dugong dugon)) are increasingly vulnerable as extreme climatic events, such as marine heatwaves and flooding, intensify with a warming climate and increasingly impact the seagrass they are dependent upon. Methods This study estimated wuthuga abundance using two methodologies: conventional observer aerial surveys, as part of a time-series of surveys, alongside aerial imagery, in Gathaagudu (Shark Bay), Western Australia in 2023. We compare the contemporary abundance estimates with long term monitoring data (1989 – 2018) to identify temporal trends in abundance and distribution. Results Over time the observer-derived estimates of wuthuga in Gathaaguda has ranged from the highest estimate in 1999 of 13929 (± SE 1652) to the lowest in 2023 of 8688 (± SE 1119). The wuthuga population has remained stable over time, with no statistical difference discernable when density is modelled. Methods were compared for the area of highest wuthuga density in 2023 (survey block 4), the observer-derived wuthuga abundance estimate was 4551 (± SE 926) and the image-derived estimate 5748 (± SE 1765). The abundance estimates yielded from both methodologies were not statistically different. For both approaches, abundance estimates were modelled using standard approaches to account for perception and availability bias. Of all wuthuga sighted in Gathaagudu in 2023, ~9.6% were calves, which is within the range of calf proportions found in past surveys. Discussion Due to wuthuga reproductive biology, the proportion of calves observed during aerial surveys may be a useful secondary indicator of population condition and seagrass availability preceding the survey. The proportion of calves observed in 2023 is an encouraging indicator of population condition. The relative stability and size of the Gathaagudu wuthuga population highlights its global importance to the persistence of the species.

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.